PENGARUH PEMANFAATAN MUSEUM MPU TANTULAR SEBAGAI SUMBER BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS X IPS 4 PADA MATERI PERKEMBANGAN MASYARAKAT PADA MASA HINDU-BUDHA DI INDONESIA DI SMA MUHAMMADIYAH 2 SIDOARJO - wicaksana, wahyu endra (Universitas Negeri Surabaya, 2018)
AbstractAlong with the increasing need to provide better teaching, also increased use of methods in providing materials to trainees. One of the methods currently considered as an interesting method is to utilize learning resources to facilitate the delivery of materials where the methods that are deemed relevant to IPS subjects are museums. The purpose of this research is to analyze the effect of MpuTantular Museum Utilization as a learning resource to the learning outcomes of the students of class X IPS 4 SMA Muhammadiyah 2 Sidoarjo on the material of